2018
DOI: 10.1038/nrclinonc.2018.28
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the PI3K pathway in cancer: are we making headway?

Abstract: The PI3K-AKT-mTOR pathway is one of the most frequently dysregulated pathways in cancer and, consequently, more than 40 compounds that target key components of this signalling network have been tested in clinical trials involving patients with a range of different cancers. The clinical development of many of these agents, however, has not advanced to late-phase randomized trials, and the antitumour activity of those that have been evaluated in comparative prospective studies has typically been limited, or toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
735
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 843 publications
(747 citation statements)
references
References 147 publications
7
735
0
5
Order By: Relevance
“…Aberrant activation of oncogenic signalling kinases and transcription factors plays a crucial role in the acquisition of hallmarks of cancer . The PI3K/Akt signalling pathway that orchestrates multiple cellular processes including cell growth, metabolism, migration and angiogenesis is one of the most commonly dysregulated pathways in malignant tumours including oral squamous cell carcinomas . Activation of PI3K induces phosphorylation of phosphatidylinositol 4,5‐bisphosphate (PIP2) to phosphatidylinositol 3,4,5‐trisphosphate (PIP3) and subsequent activation of protein kinase B (PKB) also known as Akt.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant activation of oncogenic signalling kinases and transcription factors plays a crucial role in the acquisition of hallmarks of cancer . The PI3K/Akt signalling pathway that orchestrates multiple cellular processes including cell growth, metabolism, migration and angiogenesis is one of the most commonly dysregulated pathways in malignant tumours including oral squamous cell carcinomas . Activation of PI3K induces phosphorylation of phosphatidylinositol 4,5‐bisphosphate (PIP2) to phosphatidylinositol 3,4,5‐trisphosphate (PIP3) and subsequent activation of protein kinase B (PKB) also known as Akt.…”
Section: Introductionmentioning
confidence: 99%
“…Underlying the desire to study metabolic signaling at the lysosome is the immediate realization that disruption of these pathways leads to major human pathologies. While the molecular mechanisms of lysosomal signaling in cancer, aging and immune disorders remain at their infancy, the last decade has seen the development of a numerous inhibitors targeting multiple parts of this pathway ( 195 ). While the utility of rapamycin in a handful disorders is clear, its overall success in preventing cancer growth remains poor.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Konopleva’s group demonstrated that hypoxia conditions activate the Akt/mTOR pathway, while exposure to everolimus—one of the first mTOR inhibitors that were approved by the FDA for clinical use in the treatment of patients with cancer [31]—deactivates HIF1α, reverting the glycolytic phenotype of the ALL cell line [32]. Interestingly, Konopleva, et al also reported that the Akt/mTOR pathway is strongly activated by co-culturing leukemia cells with mesenchymal stem cells in hypoxic conditions [32]; this observation is coherent with the idea that confers to mTOR the role of coordinating signals from microenvironment and subsequently adapting metabolism to these conditions.…”
Section: Mtor Involvement In Leukemia Metabolismmentioning
confidence: 99%